The crime of political party funding in Perú: brief comments on the crimen - Ruiz Baltazar, Carmen Elena (2025)
This article aims to analyze the crime of political party funding in the Peruvian legislation, as well as the justification of its incorporation to the Criminal Code. Also, it includes brief comparative comments about the crime of money laundry and political party funding mainly to concluded the possible existence of similarities or differences between them.